Children in Japan and multimedia - Shimauchi, Yukio (The Turkish Journal of Pediatrics, 1999)
Many parents in Japan today are very concerned and have daily problems with their children over the following kind of issues concerning video games, multimedia, and similar devices. 1) Is children’s enthusiasm for video games actually harming their growth (physicially or mentally)? 2) Is there any way that video games can help children in the future? For example, will playing these games help children learn to use computers or develop their power of thought? 3) Will excessive enthusiasm for TV games undermine our basic lifestyle? Is the time they spend studying at home or playing outside actually decreasing? 4) Will the methods of communication brought about by computers, pagers, and cellular phones weaken human relations among children? 5) Will being immersed in a virtual world created by computers result in a diminished sense of reality? The causes of this uneasiness may be traced to parents’ own anxieties and concerns about the exceedingly rapid growth of the "information society" of today, together with the fact that their children are directly caught up in the deluge of this information and multimedia society. The development of media has coincided with the growth of today’s adults, but children are immersed in a media-filled environment from the day they are born. In Japan, there are now children who can play video games before even learning to write. No one can predict what kind of adults these children will grow to be in the future, and it is fair to say that the most parents and children in Japan are being tossed about on the waves of this information explosion. At this international symposium, we hope to hear the many views that are held around the world concerning children and multimedia.